Identifying mobility barriers - Caves, Richard E.; Ghemawat, Pankaj (Strategic Management Journal, 1992)
Abstract This paper uses a new (PIMS) research data base to identify the mobility barriers–the factors associated with sustained intraindustry profit differentials–in a cross‐section of industries. The exercise suggests that differentiation‐related factors play more of a role in generating intraindustry profit differentials than do cost‐related ones. It also indicates that differentiation‐related advantages tend to be absorbed into fatter margins and (in some instances) larger maket shares, while cost‐related advantages are taken primarily in the form of increases in market share.